Los planes de vida y la política indígena en la Amazonía peruana - Espinosa, Oscar (2014)
In this article the political dimension of the «planes de vida indígena» (indigenous life plans) are discussed in three cases from the Peruvian Amazon region. In these cases, the «planes de vida» have fulfilled a role in the process of indigenous self-government or in the negotiation of the indigenous agenda vis-à-vis the State. The three cases studied are those of the Achuar people, an Ashaninka local organization – the Central Asháninka del Río Ene (CARE) – and the case of AIDESEP, the national-level indigenous organization for the Amazon region in Peru.